Point of Care Ultrasound Diagnosis of Maxillary Artery Pseudoaneurysm in the Emergency Department - Stephen Alerhand; Marwa Ali; Sean Beckman (CINQUILL Medical Publishers Inc., 2024)
A pseudoaneurysm results from a tear in a vessel wall. This leads to extravasation of blood into adjacent tissue and eventual formation of a fibrous sac that maintains continuity with the lumen. These vascular injuries very rarely occur in deeper vessels of the face (e.g. maxillary artery) due to protection from structures like the bony mandible and parotid gland. If left untreated, these pseudoaneurysms can lead to infection, thromboembolism, hemorrhage, and compression of surrounding structures such as facial nerve branches. Pseudoaneurysms are typically diagnosed by advanced imaging techniques including computed tomography angiography and magnetic resonance angiography. However, these tests require time to perform and interpret, are costly, and take place outside the patient care area. Computed tomography also confers ionizing radiation. Fortunately, point of care ultrasound (POCUS) is a readily available, dynamic imaging tool that can be performed at the bedside. Here we present the first known case report of a maxillary artery pseudoaneurysm diagnosed by POCUS in the emergency department. Early differentiation from a typical hematoma led to rapid management in the form of a compression bandage, as well as expedited consultation to the appropriate services.